Prospective study of prognosis of intertrochanteric fractures with lateral wall involvement as compared to intertrochanteric fractures with intact lateral wall - Bansal, Amit (International Journal of Research in Orthopaedics, 2019)
Background: Intertrochanteric fractures with fracture lateral wall (FLW) are biomechanically unstable fractures. Methods: 40 patients who met inclusion criteria underwent surgery. Post-operatively patients were followed up for a minimum period of 24 weeks. Radiological and functional assessment was done post-operatively. Endpoints of fracture were studied thoroughly. Results: Secondary lateral wall fractures were common than primary lateral wall fractures. Functional outcome was found to be poor in FLW than intact lateral wall (ILW) group (p=0.01). HHS of ILW fracture was 70, while in FLW it was 46. Displacement was found to be a better radiological parameter to assess reduction quality (p=0.02) than neck shaft angle. Implant position with Cleveland method was found to be a better predictor of fixation quality than tip apex distance. There were 6 (15%) mechanical failures. Screw cut out (3 cases) found to be most common mechanical complication (7.5%). There were four failures (33%) in FLW. Secondary lateral wall fractures were found to have poor prognosis than primary lateral wall fractures. A2.3 was found to have more chance of conversion to A3 due to thinned out lateral wall. Many of them happened when DHS was the implant of choice (60%). Conclusions: Functional outcome of FLW is poor than ILW. Secondary lateral wall fractures have worse prognosis than primary lateral wall fractures. Fragment specific fixation is difficult in secondary lateral wall fractures as compare to primary lateral wall fracture, due to higher comminution.